The Effect of Real Business Cycle on Islamic Capital Market Resilience in Indonesia - Ibrahim, Muhammad Yusuf; Indra, Indra; Satifa, Siti Annisa (International Journal of Islamic Economics and Finance (IJIEF), 2025)
In an era of increasing economic volatility and financial uncertainty, understanding the impact of the Real Business Cycle (RBC) on the Islamic Capital Market (ICM) is crucial for enhancing the resilience of Islamic financial systems, which are increasingly significant in global finance. This research is important because understanding the impact of the Real Business Cycle (RBC) on the Islamic Capital Market (ICM) is crucial for enhancing the resilience of Islamic financial systems, which are increasingly significant in global finance. The research aims to investigate the extent of co-movement and the effect of the Real Business Cycle (RBC) on the Islamic Capital Market (ICM) in Indonesia. The methodology begins with the Hodrick-Prescott (HP) Filter to identify trends and cycles in the RBC and ICM data. Next, cross-correlation analysis is used to measure the co-movement between the two, determining how RBC fluctuations affect the Islamic capital market. Finally, the Vector Autoregressive (VAR) and Vector Error Correction Model (VECM) are applied to explore both the short-term and long-term causal relationships between RBC and ICM, offering insights into immediate and persistent effects on the market.  The findings reveal a significant relationship between Real Business Cycle (RBC) indicators and the Islamic Capital Market (ICM), with notable shifts in investor behavior and varying impacts of GDP, unemployment, and exchange rates on Islamic financial instruments like Jakarta Islamic Index (JII) and Sukuk.